STRATEGI PENINGKATAN DAYA SAING PT ‘ABCD’ TBK. DI INDUSTRI MAKANAN OLAHAN PADA TAHUN 2015 - Kanya Lakshmi Sidarta; Rina Oktaviani; Kirbrandoko Kirbrandoko (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The distribution of market share of Indonesia's processed food industry is dominated by only a few companies, i.e. one company representing 20% of market share, three companies representing 10% of market share, and 124 companies representing 35% of shares (2013, LEK insights). This condition is also shown by there are only 15 companies which are listed in Indonesian Stock Exchange (BEI) as sub-sectors of food and beverages. CV 'ABCD', known as the 'ABCD', is one of the companies listed on the BEI on the sub-sectors of food and beverages. Thus, the purposes of this study were to examine the factors influencing the competition in the processed food industry in Indonesia, to analyze the competitiveness of 'ABCD' among other competing companies listed on BEI, and to propose alternative strategies to improve the competitiveness of 'ABCD' within the developing and challenging market. The analytical tools used in the study were Porter's Diamond Model, Firm Value Creation and AHP. The results showed that the factors affecting the competitiveness of the processed food industry in Indonesia, in reference to Porter's Diamond Model, is the availability of products (good quality & innovative), the number of requests, the decision-making process with a clear purpose, value creation, and good internal and external relations. The alternative strategy proposed in enhancing the competitiveness of 'ABCD' is improving quality standards in an integrated system by the CEO (owner) and Director of Marketing as the main actors in the clear decision process.Keywords: AHP, competitiveness, diamond porter, processed food industry, BEI